Leptospiral lipopolysaccharide stimulates the expression of toll‐like receptor 2 and cytokines in pig fibroblasts. (14th July 2014) - Guo, Yijie; Fukuda, Tomokazu; Donai, Kenichiro; Kuroda, Kengo; Masuda, Mizuki; Nakamura, Shuichi; Yoneyama, Hiroshi; Isogai, Emiko
Abstract Pigs throughout the world are afflicted with leptospirosis, causing serious economic losses and potential hazards to human health. Although it has been known that leptospiral lipopolysaccharide (L‐LPS) is involved in an immunological reaction between an antigen and a host cell, little is known about how the immune system of pigs can respond to L‐LPS. Here, we stimulated pig fibroblasts by L‐LPS and then quantitatively measured gene and protein expression levels of two toll‐like receptors (TLRs), TLR2 and TLR4, by real‐time PCR and Western blotting. As a result, expression of TLR2 was found to be significantly up‐regulated within 24 h after L‐LPS stimulation whereas induction of TLR4 expression was relatively weak. We also revealed that of myeloid differentiation primary response gene 88 (MyD88), interleukin 6 (IL‐6) and IL‐8 gene expressions were markedly up‐regulated by L‐LPS stimulation. These results may suggest that the pig cell can activate TLR2 rather than TLR4 by L‐LPS stimulation, thereby inducing expression of cytokines.